Exploring the impact of digital entrepreneurship education among graduates in Bangladesh - Al-Mamun, Abdullah; Olowolayemo, Akeem; Sharyar, Wani; Mohamed Sofiadin, Aidrina (IIUM Press, 2022)
Unemployment, especially among graduates, is a big issue not only in individual countries but also globally. Digital entrepreneurship is proposed as a way to mitigate, if not completely remove, the hardships of unemployment for both individuals and governments. It has been demonstrated that becoming an entrepreneur is a conscious decision that necessitates a great deal of thought and planning. The current study incorporates cognitive and behavioural school of thought principles to develop a model that connects digital entrepreneurship education to graduate entrepreneurial intention. The attribute approach appears to imply that entrepreneurship is a privilege associated with certain characteristics, and digital entrepreneurship education will assist in the development of entrepreneurs. In light of the above findings, the current study examined the impact of digital entrepreneurship education on entrepreneurship among Bangladeshi graduates using the Theory of Planned Behaviour (TPB). The proposed framework illustrates that entrepreneurship education is a conscious strategy and that there is a link between digital entrepreneurship education and entrepreneurship intention, which is mediated by personal attitude (PA),subjective norm (SN), perceived behavioural control (PBC), and entrepreneurial decision (ED). This study employs a quantitative approach to address a methodological gap in the literature, which usually evaluates simply entrepreneurship intention instead of the actual process of entrepreneurship. Data were collected from several university students representing several study disciplines in Bangladesh and structural equation modelling was used to test the hypothesized model and structural relationships. The empirical findings and recommendations show that graduates' entrepreneurial intentions have a positive impact on their attitudes, subjective norms, perceived behavioural control, and entrepreneurial intentions, and that this information can assist policymakers, government officials, entrepreneurship experts, and lecturers decide to include digital entrepreneurship courses in higher education institutions.